The Depiction of Black and White Women Relation in Mrs. Lincoln's Dressmaker Novel written by Jennifer Chiaverini - Olivia Herin Tanaboleng (ELITE: Journal of English Language and Literature, 2018)
This study tried to analyze black and white women’s depiction in the novel Mrs. Lincoln’s Dressmaker (2013) written by Jennifer Chiaverini. This study used a descriptive qualitative method by approaching the data from hegemony perspective. It is assumed that the depiction of black and white women in the novel was having an ideological power in order to strengthen white supremacy as well as black stereotype. The sources of data in this study consisted of primary data; the text of the novel Mrs. Lincoln’s Dressmaker and secondary data was taken from the memoir of Elizabeth Keckley; Behind the Scene: Thirty Years a Slave, or, Four Years in the White House. The researcher collected the data by reading, take-noting, identifying, and grouping the data. The data analysis technique is describing, interpreting, analyzing, and concluding the analysis. This study found that, first, the depiction of black and white women. The black woman is depicted as skilled and beautiful in the beauty standard of white women; White woman is depicted as a beautiful woman who is good at politics, second, the relation of those women in the context of position; Mistress vs Servant and Deceiver vs Deceived. Mistress is depicted through the white woman character, while the servant is depicted through the black character. The deceiver is depicted through the white woman, while the deceived is a black woman. This study claimed that the novel Mrs. Lincoln’s Dressmaker is a medium to build and maintain the white ideology by rewriting the black memoir.